A method for evaluating thermal conductivity of main insulation of generator stator bars
By using the thermal conductivity test fluid and curing glue on the main insulating material of the generator stator wire rod, combined with specific calculation formulas, the problem that the existing test methods cannot quickly and accurately evaluate the thermal conductivity, achieving simplicity and efficiency Thermal conductivity test.
Patent Information
- Application Number
- CN202211010350.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-08-23
AI Technical Summary
The existing testing methods cannot quickly and accurately evaluate the thermal conductivity of the main insulation of the generator stator wire rod, and there are problems such as time-consuming, labor-intensive and cost-effective.
By fully immersing the glass fiber mica tape with a thermal conductivity test solution, and measuring the basic thermal conductivity of the raw materials under different external conditions, testing with the thermal procedure of the curing glue solution, a specific formula is used to calculate the thermal conductivity parameters.
The thermal conductivity of the generator stator rod main insulation is achieved with a simple and fast and accurate evaluation, avoiding tedious steps and high costs, and the test results are consistent with the traditional methods and have high accuracy.
Smart Images

Figure BDA0003810298110000071 
Figure BDA0003810298110000091 
Figure FDA0005153743820000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of testing methods, and in particular relates to a method for evaluating the thermal conductivity of the main insulation of a generator stator bar. Background Art
[0002] The main insulation of the generator stator bar is made of glass fiber mica tape impregnated with curing glue, and then prepared by winding, baking and other processes. It is an important part of the generator. Since the main insulation of the generator stator bar needs to have good thermal conductivity, the test of the thermal conductivity of the main insulation is extremely important and is one of the important indicators for evaluating the performance of the main insulation material.
[0003] Many standards have been provided at home and abroad for testing the thermal conductivity and heat transfer characteristics of some samples, such as: ASTM D5470-06 (2011) Standard Test Method for Thermal Transmission Properties of Thermally Conductive Electrical Insulation Materials, a test method for the thermal transfer characteristics of thermally conductive electrical insulation materials, proposes a method for testing the thermal conductivity of samples using a steady-state heat flow method; GB / T 22588-2008 Flash Method for Measuring Thermal Diffusivity or Thermal Conductivity, proposes a method for testing the thermal conductivity of samples using a steady-state heat flow method; ASTM-E1461 Test Method for Determining the Thermal Diffusivity of Solids by Flash Method (Laser Flash Method), proposes a method for testing the thermal conductivity of samples by laser flash method; ASTM-E1530 Test Method for Evaluating the Thermal Transfer Resistance of Materials by Using Thermally Guarded Heat Flow Meter Technology, proposes a method for evaluating thermal conductivity by using thermally guarded heat flow meter technology. However, the above test standards all have the problems of high test cost, long test time and relatively stringent requirements on the measurement environment, and are not suitable for testing the thermal conductivity of the main insulation of the generator stator bars.
[0004] In addition, many patent documents also disclose thermal conductivity test methods applicable to various materials. For example, patent document CN 103267774 B discloses a method for testing the thermal conductivity of pipes, which uses a tester to test the thermal conductivity of sample pipes, solving the problem that the thermal conductivity of current plastic pipe products cannot be tested, allowing companies to conveniently, scientifically and intuitively test product performance during the production process, filling the corresponding technical gap.
[0005] Patent document CN 110220940 B discloses a method for testing the thermal conductivity of irregular samples. The method is to place the sample to be tested in three states: a constant temperature T0 state, a constant temperature T1 state with a strong convection heat transfer coefficient on the surface, and a surface insulation state, to construct a non-steady-state heat transfer process between the inside of the sample to be tested and the environment; the test uses the energy storage of the sample to be tested as a heat source or heat sink to achieve internal and external heat transfer testing without damaging the sample, which can avoid the heat shielding effect caused by the good thermal conductive material on the surface of the uneven sample, and can also solve the heating problem caused by the irregular shape of the sample. This method can be used for non-destructive testing of the thermal conductivity of irregular-shaped samples that are difficult to detect using conventional methods.
[0006] Patent document CN 113092523 A discloses a method for testing the thermal conductivity of thin film materials. The method uses a heating element and a cooling element on an insulated test platform to establish a temperature field that does not change with time in the film material to be tested, so that it reaches a one-dimensional steady-state conduction state, and then uses a temperature measuring element to measure the temperature gradient of the film material to be tested, and then calculates the heat flux and thermal conductivity. This method solves the problems of high testing cost, inability to test the heat flux of thin film materials, and inability to intuitively characterize the heat flux and heat dissipation performance of films of different thicknesses in the existing laser flash method for characterizing the heat dissipation performance of thin film materials; it also solves the problems of low measurement accuracy and great influence of the external environment in detecting the temperature and heat transfer conditions at different positions on the film using the heating method.
[0007] Patent document CN 111122647 A discloses a method for testing the thermal conductivity of lithium-ion battery pole pieces. This method can only be used to test and evaluate the thermal conductivity of pole pieces (including positive pole pieces and negative pole pieces), and is not applicable to the thermal conductivity of other materials.
[0008] It can be seen from the above patent documents that the thermal conductivity test of various materials is specific, and the existing test methods cannot be applied to all materials. In particular, the main insulation material of the generator stator wire bar has the characteristics of complex preparation process and cumbersome steps. The above test method is not suitable for the thermal conductivity test of this type of material. Even if the test method can be used, the accuracy of the test result is low. How to quickly and accurately evaluate the thermal conductivity of the main insulation of the generator stator wire bar is of great significance.
[0009] In order to obtain the thermal conductivity parameters of the main insulation of the generator stator wire bar, the existing method usually takes a lot of time to prepare various main insulation samples from beginning to end according to the actual preparation process, and then the thermal conductivity coefficient of all samples is tested to finally obtain a more accurate method for evaluating the thermal conductivity of the main insulation of the generator stator wire bar. Obviously, the current testing method is time-consuming, labor-intensive and costly.
[0010] Therefore, how to provide a method for evaluating the thermal conductivity of the main insulation of the stator wire bar of a generator, which is simple, fast, and can accurately evaluate the thermal conductivity of the main insulation, in order to solve the problem that other existing thermal conductivity test methods cannot be used for the actual measurement of the thermal conductivity of the main insulation of the stator wire bar of the generator, has become a technical problem to be solved urgently in the present invention.
[0011] However, Summary of the invention
[0012] The purpose of the present invention is to solve the above technical problems, thereby providing a method for evaluating the thermal conductivity of the main insulation of the stator wire bar of a generator. The technical purpose of the present invention is to solve the problem that the existing methods are time-consuming and labor-intensive, costly, and have inaccurate test results, and cannot be applied to the accurate test of the thermal conductivity of the main insulation of the stator wire bar of a generator.
[0013] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0014] A method for evaluating the thermal conductivity of the main insulation of a generator stator bar comprises the following steps:
[0015] (1) Use thermal conductivity test liquid to fully soak the main insulation glass fiber mica tape of the generator stator bar. After soaking, take out the glass fiber mica tape, wipe its surface dry and then test the thermal conductivity coefficient in the thickness direction to obtain the thermal conductivity coefficient A of the glass fiber mica tape after soaking in thermal conductivity test liquid. Thermal ;
[0016] (2) The glass fiber mica tape is fully soaked in the curing glue used for the main insulation of the generator stator bar. After soaking, it is taken out and the surface is wiped dry before the thermal conductivity test in the thickness direction is performed to obtain the thermal conductivity B of the glass fiber mica tape after soaking in the thermal conductivity test liquid. Thermal ;
[0017] (3) The curing glue used for the main insulation of the generator stator bar is heated and cured, and then the thermal conductivity coefficient of the cured sample in the thickness direction is tested to obtain the thermal conductivity coefficient C of the cured sample in the thickness direction under the curing conditions. Thermal ;
[0018] (4) Calculate the thermal conductivity parameter P of the main insulation of the generator stator bar according to the following formula: Thermal :
[0019]
[0020] In the formula: liquid1 to liquidn represent the thermal conductivity test liquid used, which is composed of 1 to n liquids, where n ≥ 1; m liquid1 To m liquidnRepresents the molecular weight of the first to nth liquids; H liquid1 To H liquidn Represents the solubility parameter of the corresponding liquid.
[0021] The present invention innovatively proposes a new method for accurately evaluating the thermal conductivity of the main insulation by measuring the basic thermal conductivity of the raw materials under different external conditions and then using the formula designed by the present invention for calculation. The testing method of the present invention is simple and fast, and the results are consistent with those obtained by traditional methods, with the advantage of high accuracy. The evaluation method provided by the present invention can accurately and efficiently evaluate the thermal conductivity of the main insulation of the stator wire rods of the generator, without the need to prepare the main insulation finished product through cumbersome steps and then take samples for thermal conductivity testing.
[0022] Furthermore, the thermal conductivity test liquid in step (1) includes at least one of the following liquids: isobutyl acetate, methylcyclohexane, 1,2-dichloroethane, turpentine, n-octanol, methyl isobutyl ketone, isobutanol, dimethylacetamide, carbon tetrachloride, isopropanol, dimethyl sulfoxide, formic acid, tetralin, cyclohexanone, cyclohexane, amyl acetate, n-hexanol, cresol, cyclohexanol, n-butanol, xylene, acetic acid, phenol, glycerol, n-heptane, ethyl isobutyrate, butyl acetate, dipentene, pyridine, piperidine, n-propanol, toluene, water or ethylene glycol; when the thermal conductivity test liquid is a plurality of liquids, the molar amount of each liquid is the same.
[0023] Furthermore, the thermal conductivity test standards in steps (1) to (3) are tested according to "ASTM-E1461, ASTMD5470-06".
[0024] Furthermore, the curing step in step (3) is as follows: 1) heating the adhesive to be cured to a curing temperature of T cur1 , curing time is t cur1 , and perform the first isothermal curing treatment; 2) cool to room temperature and stay for 2-10 minutes, then heat up to the curing temperature T cur2 , curing time is t cur2 , and perform a second isothermal curing treatment; 3) cool to room temperature and stay for 2-10 minutes, then heat to the curing temperature T cur3 , curing time is t cur3 , and perform a third isothermal curing treatment; 4) finally cool to room temperature to complete curing and obtain a cured sample, wherein the heating and cooling rates are both 5-10°C / min.
[0025] Furthermore, the curing temperature T cur1 , T cur2 and T cur3They are the peak curing temperatures of the glue at heating rates of 40°C / min, 10°C / min and 2°C / min, respectively, in degrees Celsius.
[0026] Furthermore, the peak curing temperature is tested by differential scanning calorimetry.
[0027] Furthermore, the curing time t cur1 ,t cur2 and t cur3 The values of (T cur1 -40)min, (T cur2 -10)min and (T cur3 -2)min.
[0028] The beneficial effects of the present invention are as follows:
[0029] (1) The present invention proposes for the first time a method for evaluating the thermal conductivity of the main insulation of a generator stator bar. The method measures the basic thermal conductivity of the raw materials under different external conditions and then uses the formula designed by the present invention to calculate, thereby accurately evaluating the thermal conductivity of the main insulation;
[0030] (2) The evaluation method provided by the present invention does not require cumbersome steps to prepare the main insulation product and then take samples for thermal conductivity testing. It is simple and fast, and is consistent with the results obtained by traditional methods, with the advantage of high accuracy. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0032] The thermal conductivity test liquids and their corresponding physical parameters involved in the following embodiments of the present invention are shown in Table 1:
[0033] Table 1
[0034]
[0035] Example 1
[0036] The present invention provides a method for evaluating the thermal conductivity of the main insulation of a generator stator bar, comprising the following steps:
[0037] (1) The glass fiber mica tape used for the main insulation is fully soaked in thermal conductivity test liquid turpentine, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out according to ASTM-E1461, and the thermal conductivity coefficient A of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =0.21W / (m·K). According to the data, the molecular weight of the turpentine oil is m liquid =136.23 g / mol, solubility parameter H liquid =8.1(cal / cm 3 ) 1 / 2 ;
[0038] (2) The glass fiber mica tape used for the main insulation is fully soaked in the curing glue used for the main insulation, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out in accordance with ASTM-E1461, and the thermal conductivity coefficient B of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =0.63W / (m·K);
[0039] (3) The curing glue used for the main insulation is cured according to the corresponding thermal program, and then the thermal conductivity of the cured sample in the thickness direction is tested. The test standard is carried out according to ASTM-E1461, and the thermal conductivity C of the cured glue in the thickness direction is obtained. Thermal =0.08W / (m·K).
[0040] The thermal program used in this embodiment includes the following steps: first, a differential scanning calorimeter is used to perform a temperature curing test on the curing glue at different heating rates, and the curing peak temperatures at heating rates of 40°C / min, 10°C / min and 2°C / min are 178°C, 154°C and 120°C respectively. Then, the curing glue is introduced into the mold and heated to the first curing temperature T cur1 = 178°C and curing time is t cur1 = 138min isothermal curing, then cooled to room temperature and left for 10min, then heated to the second curing temperature T cur2 = 154°C and curing time is t cur2 = 144min isothermal curing, then cooled to room temperature and kept for 10min, then heated to the third curing temperature T cur3 = 120℃ and curing time is t cur3 = 118min of isothermal curing, and finally cooling to room temperature to complete curing to obtain a cured sample, wherein the heating and cooling rate in the above curing thermal program is 5°C / min;
[0041] (4) Calculate the thermal conductivity parameters of the generator stator bar main insulation according to the following formula:
[0042] According to the above method, the thermal conductivity of 50 generator stator bar main insulation samples of the same production batch is calculated, and then the average value is taken to calculate the thermal conductivity parameter P of the generator stator bar main insulation. Thermal =0.398.
[0043] For another 50 generator stator wire bar main insulation samples of the same production batch in this embodiment, the thermal conductivity coefficient is tested by the following traditional method: the main insulation is prepared according to the actual manufacturing process, through winding, baking, sample preparation and other processes, and then the thermal conductivity performance test is performed, and the average value is taken to obtain the thermal conductivity coefficient of 0.399W / (m·K). By comparing the test results of the two, it is proved that the result obtained by using the formula of the present invention is accurately calculated, and the thermal conductivity performance parameters obtained by testing the main insulation parts prepared through complex links are consistent with each other and have high accuracy.
[0044] Example 2
[0045] A method for evaluating the thermal conductivity of the main insulation of a generator stator bar comprises the following steps:
[0046] (1) The glass fiber mica tape used for the main insulation was fully soaked in a thermal conductivity test liquid, a mixed solution of methyl cyclohexane and ethyl isobutyrate in an equal molar ratio, and then its surface was wiped dry and the thermal conductivity coefficient in the thickness direction was tested. The test standard was carried out in accordance with ASTM-E1461, and the thermal conductivity coefficient A of the glass fiber mica tape after soaking in the thermal conductivity test liquid was obtained. Thermal =1.1W / (m·K). According to the data, the molecular weight of methylcyclohexane is m liquid1 =98.18 g / mol, solubility parameter H liquid1 =7.8(cal / cm 3 ) 1 / 2 , while the molecular weight of ethyl isobutyrate is m liquid2 =98.18 g / mol, solubility parameter H liquid2 =7.8(cal / cm 3 ) 1 / 2 ;
[0047] (2) The glass fiber mica tape used for the main insulation is fully soaked in the curing glue used for the main insulation, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient B of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =0.72W / (m·K);
[0048] (3) The curing glue used for the main insulation is cured according to a specially designed thermal program, and then the thermal conductivity of the cured sample in the thickness direction is tested. The test standard is based on the relevant test standard of ASTM-E1461, and the thermal conductivity C of the cured glue in the thickness direction is obtained. Thermal =0.12W / (m·K). The specially designed thermal program includes the following steps: first, a differential scanning calorimeter is used to perform a temperature curing test on the curing glue at different heating rates, and the peak curing temperatures at heating rates of 40℃ / min, 10℃ / min and 2℃ / min are 213℃, 190℃ and 142℃ respectively. Then, the curing glue is introduced into the mold and heated to the first curing temperature T cur1 = 213℃ and curing time is t cur1 = 173min of isothermal curing, then cooled to room temperature and left for 5min, then heated to the second curing temperature T cur2 = 190℃ and curing time is t cur2 = 180min isothermal curing, then cooling to room temperature and staying for 5min, then heating to the third curing temperature T cur3 = 142°C and curing time is t cur3 =140min isothermal curing, and finally cooling to room temperature to complete curing to obtain a cured sample, wherein the heating and cooling rate in the above curing thermal program is 8°C / min;
[0049] (4) Calculate the thermal conductivity parameters of the generator stator bar main insulation according to the following formula:
[0050]
[0051] According to the above method, the thermal conductivity of 50 generator stator wire bar main insulation samples from different production batches (two batches, a total of 100 samples) was calculated, and then the average value was taken to calculate the thermal conductivity parameter P of the generator stator wire bar main insulation. Thermal =1.130.
[0052] In the materials of the above two production batches, 50 generator stator wire rod main insulation samples were selected respectively, and their thermal conductivity coefficients were tested by the following traditional method: the main insulation was prepared according to the actual manufacturing process, through winding, baking, sample preparation and other processes, and then the thermal conductivity performance was tested, and the average value was taken to obtain the thermal conductivity coefficient of 1.131W / (m·K). By comparing the test results of the two, it is proved that the result obtained by using the formula of the present invention is accurate in calculation, and has good consistency and high accuracy with the thermal conductivity performance parameters obtained by testing the main insulation parts prepared through complex links.
[0053] Example 3
[0054] A method for evaluating the thermal conductivity of the main insulation of a generator stator bar comprises the following steps:
[0055] (1) The glass fiber mica tape used for the main insulation was fully soaked in a thermal conductivity test liquid, a mixed solution of water and ethylene glycol in an equal molar ratio, and then its surface was wiped dry and the thermal conductivity coefficient in the thickness direction was tested. The test standard was carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient A of the glass fiber mica tape after soaking in the thermal conductivity test liquid was obtained. Thermal =0.99W / (m·K). According to the data, the molecular weight of water is m liquid1 =18 g / mol, solubility parameter H liquid1 =23.4(cal / cm 3 ) 1 / 2 , and the molecular weight of ethylene glycol is m liquid2 =62g / mol, solubility parameter H liquid2 =7.9(cal / cm 3 ) 1 / 2 ;
[0056] (2) The glass fiber mica tape used for the main insulation is fully soaked in the curing glue used for the main insulation, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient B of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =1.34W / (m·K);
[0057] (3) The curing glue used for the main insulation is cured according to a specially designed thermal program, and then the thermal conductivity of the cured sample in the thickness direction is tested. The test standard is based on the relevant test standard of ASTM-E1461, and the thermal conductivity C of the cured glue in the thickness direction is obtained. Thermal =0.19W / (m·K). The specially designed thermal program includes the following steps: first, a differential scanning calorimeter is used to perform a temperature curing test on the curing glue at different heating rates, and the peak curing temperatures at heating rates of 40°C / min, 10°C / min and 2°C / min are 125°C, 115°C and 103°C respectively. Then, the curing glue is introduced into the mold and heated to the first curing temperature T cur1 = 125℃ and curing time is t cur1 = 85min isothermal curing, then cooled to room temperature and kept for 8min, then heated to the second curing temperature T cur2 = 115℃ and curing time is t cur2 = 105min isothermal curing, then cooled to room temperature and kept for 8min, then heated to the third curing temperature T cur3= 103°C and curing time is t cur3 =101min isothermal curing, and finally cooling to room temperature to complete curing to obtain a cured sample, wherein the heating and cooling rate in the above curing thermal program is 6°C / min;
[0058] (4) Calculate the thermal conductivity parameters of the generator stator bar main insulation according to the following formula:
[0059]
[0060] According to the above method, the thermal conductivity of 200 generator stator bar main insulation samples of the same production batch was calculated, and then the average value was taken to calculate the thermal conductivity parameter P of the generator stator bar main insulation. Thermal =0.930.
[0061] For another 200 generator stator wire bar main insulation samples of the same production batch in the embodiment, the thermal conductivity coefficient is tested by the following traditional method: the main insulation is prepared according to the actual manufacturing process, through winding, baking, sample preparation and other processes, and then the thermal conductivity performance test is performed, and the average value is taken to obtain the thermal conductivity coefficient of 0.932W / (m·K). By comparing the test results of the two, it is proved that the result obtained by using the formula of the present invention is accurately calculated, and the thermal conductivity parameters obtained by testing the main insulation parts prepared through complex links are consistent with each other and have high accuracy.
[0062] Example 4
[0063] A method for evaluating the thermal conductivity of the main insulation of a generator stator bar comprises the following steps:
[0064] (1) The glass fiber mica tape used for the main insulation was fully soaked in a thermal conductivity test liquid, a mixed solution of isopropyl alcohol and n-octanol in an equal molar ratio, and then its surface was wiped dry and the thermal conductivity coefficient in the thickness direction was tested. The test standard was carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient A of the glass fiber mica tape after soaking in the thermal conductivity test liquid was obtained. Thermal =1.82W / (m·K). According to the data, the molecular weight of isopropyl alcohol is m liquid1 =60.09 g / mol, solubility parameter H liquid1 =11.5(cal / cm 3 ) 1 / 2 , and the molecular weight of n-octanol is m liquid2 =130.22 g / mol, solubility parameter H liquid2 =10.3(cal / cm 3 ) 1 / 2 ;
[0065] (2) The glass fiber mica tape used for the main insulation is fully soaked in the curing glue used for the main insulation, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient B of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =1.99W / (m·K);
[0066] (3) The curing glue used for the main insulation is cured according to a specially designed thermal program, and then the thermal conductivity of the cured sample in the thickness direction is tested. The test standard is based on the relevant test standard of ASTM-E1461, and the thermal conductivity C of the cured glue in the thickness direction is obtained. Thermal =0.28W / (m·K). The specially designed thermal program includes the following steps: first, a differential scanning calorimeter is used to perform a temperature curing test on the curing glue at different heating rates, and the peak curing temperatures at the heating rates of 40℃ / min, 10℃ / min and 2℃ / min are 164℃, 135℃ and 121℃ respectively. Then, the curing glue is introduced into the mold and heated to the first curing temperature T cur1 = 164°C and curing time is t cur1 = 124min isothermal curing, then cooled to room temperature and kept for 5min, then heated to the second curing temperature T cur2 = 135℃ and curing time is t cur2 = 125min isothermal curing, then cool to room temperature and stay for 5min, then heat to the third curing temperature T cur3 = 121°C and curing time is t cur3 = 119 min of isothermal curing, and finally cooling to room temperature to complete curing to obtain a cured sample, wherein the heating and cooling rate in the above curing thermal program is 9°C / min;
[0067] (4) Calculate the thermal conductivity parameters of the generator stator bar main insulation according to the following formula:
[0068]
[0069] According to the above method, the thermal conductivity of 30 generator stator wire bar main insulation samples from three different production batches was calculated, and then the average value was taken to calculate the thermal conductivity parameter P of the generator stator wire bar main insulation. Thermal =2.090.
[0070] 20 generator stator wire bar main insulation samples were randomly selected from the three different production batches, and their thermal conductivity was tested by the following traditional method: the main insulation was prepared according to the actual manufacturing process, through winding, baking, sample preparation and other processes, and then the thermal conductivity test was performed, and the average value was taken to obtain a thermal conductivity of 2.092W / (m·K), which proves that the result obtained by using the formula of the present invention is accurate, and has good consistency and high accuracy with the thermal conductivity parameters obtained by testing the main insulation parts prepared through complex links.
[0071] Example 5
[0072] A method for evaluating the thermal conductivity of the main insulation of a generator stator bar comprises the following steps:
[0073] (1) The glass fiber mica tape used for the main insulation was fully soaked in the thermal conductivity test liquid butyl acetate, and then its surface was wiped dry and the thermal conductivity coefficient in the thickness direction was tested. The test standard was carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient A of the glass fiber mica tape after soaking in the thermal conductivity test liquid was obtained. Thermal =0.35W / (m·K). According to the data, the molecular weight of butyl acetate is m liquid =116.16 g / mol, solubility parameter H liquid =8.2(cal / cm 3 ) 1 / 2 ;
[0074] (2) The glass fiber mica tape used for the main insulation is fully soaked in the curing glue used for the main insulation, and then its surface is wiped dry and the thermal conductivity coefficient in the thickness direction is tested. The test standard is carried out in accordance with the relevant test standard of ASTM-E1461, and the thermal conductivity coefficient B of the glass fiber mica tape after soaking in the thermal conductivity test liquid is obtained. Thermal =0.52W / (m·K);
[0075] (3) The curing glue used for the main insulation is cured according to a specially designed thermal program, and then the thermal conductivity of the cured sample in the thickness direction is tested. The test standard is based on the relevant test standard of ASTM-E1461, and the thermal conductivity C of the cured glue in the thickness direction is obtained. Thermal =0.14W / (m·K). The specially designed thermal program includes the following steps: first, a differential scanning calorimeter is used to perform a temperature curing test on the curing glue at different heating rates, and the peak curing temperatures at heating rates of 40℃ / min, 10℃ / min and 2℃ / min are 170℃, 159℃ and 111℃ respectively. Then, the curing glue is introduced into the mold and heated to the first curing temperature T cur1 = 170℃ and curing time is t cur1= 130min isothermal curing, then cooled to room temperature and left for 10min, then heated to the second curing temperature T cur2 = 159°C and curing time is t cur2 = 149min isothermal curing, then cooled to room temperature and kept for 10min, then heated to the third curing temperature T cur3 = 111°C and curing time is t cur3 =109min isothermal curing, and finally cooling to room temperature to complete curing to obtain a cured sample, wherein the heating and cooling rate in the above curing thermal program is 5°C / min;
[0076] (4) Calculate the thermal conductivity parameters of the generator stator bar main insulation according to the following formula:
[0077]
[0078] According to the above method, 20, 50 and 100 generator stator wire bar main insulation samples were taken from three different production batches, and the thermal conductivity was calculated. Then the average value was taken to calculate the thermal conductivity parameter P of the generator stator wire bar main insulation. Thermal =0.530.
[0079] For the above three different production batches, 50, 30 and 90 generator stator wire bar main insulation samples were selected respectively, and their thermal conductivity coefficients were tested by the following traditional method: the main insulation was prepared according to the actual manufacturing process, through winding, baking, sample preparation and other processes, and then the thermal conductivity performance was tested, and the average value was taken to obtain a thermal conductivity coefficient of 0.531W / (m·K), which proved that the result obtained by using the formula of the present invention is accurate in calculation, and has good consistency and high accuracy with the thermal conductivity performance parameters obtained by testing the main insulation parts prepared through complex links.
Claims
1. A method for evaluating the thermal conductivity of the main insulation of a generator stator bar, characterized in that: The following steps are involved: (1) Use thermal conductivity test liquid to fully soak the main insulation glass fiber mica tape of the generator stator bar. After soaking, take out the glass fiber mica tape, wipe its surface dry and then test the thermal conductivity coefficient in the thickness direction to obtain the thermal conductivity coefficient A of the glass fiber mica tape after soaking in thermal conductivity test liquid. Thermal ; Wherein, the thermal conductivity test liquid includes at least one of the following liquids: isobutyl acetate, methylcyclohexane, 1,2-dichloroethane, turpentine, n-octanol, methyl isobutyl ketone, isobutyl alcohol, dimethylacetamide, carbon tetrachloride, isopropyl alcohol, dimethyl sulfoxide, formic acid, tetralin, cyclohexanone, cyclohexane, amyl acetate, n-hexanol, cresol, cyclohexanol, n-butanol, xylene, acetic acid, phenol, glycerol, n-heptane, ethyl isobutyrate, butyl acetate, dipentene, pyridine, piperidine, n-propanol, toluene, water or ethylene glycol; when the thermal conductivity test liquid is a plurality of liquids, the molar amount of each liquid is the same; (2) The glass fiber mica tape is fully soaked in the curing glue used for the main insulation of the generator stator bar. After soaking, it is taken out and the surface is wiped dry before the thermal conductivity test in the thickness direction is performed to obtain the thermal conductivity B of the glass fiber mica tape after soaking in the thermal conductivity test liquid. Thermal ; (3) The curing glue used for the main insulation of the generator stator bar is heated and cured, and then the thermal conductivity coefficient of the cured sample in the thickness direction is tested to obtain the thermal conductivity coefficient C of the cured sample in the thickness direction. Thermal ; (4) Calculate the thermal conductivity parameter P of the main insulation of the generator stator bar according to the following formula: Thermal : In the formula: liquid1 to liquidn represent the thermal conductivity test liquid used, which is composed of 1 to n liquids, where n ≥ 1; m liquid1 To m liquidn Represents the molecular weight of the first to nth liquids; H liquid1 To H liquidn Represents the solubility parameter of the corresponding liquid.
2. The evaluation method according to claim 1, characterized in that: The thermal conductivity test standard in steps (1) to (3) is tested according to "ASTM-E1461".
3. The evaluation method according to claim 1, characterized in that: The curing step in step (3) is as follows: 1) heating the adhesive to be cured to a curing temperature of T cur1 , curing time is t cur1 , and perform the first isothermal curing treatment; 2) cool to room temperature and stay for 2 to 10 minutes, then heat up to the curing temperature T cur2 , curing time is t cur2 , and perform a second isothermal curing treatment; 3) cool to room temperature and stay for 2-10 minutes, then heat to the curing temperature T cur3 , curing time is t cur3 , and a third isothermal curing treatment is carried out; finally, the temperature is lowered to room temperature to complete the curing and obtain a cured sample, wherein the heating and cooling rates are both 5-10°C / min.
4. The evaluation method according to claim 3, characterized in that: The curing temperature T cur1 , T cur2 and T cur3 They are the curing peak temperatures of the glue at heating rates of 40℃ / min, 10℃ / min and 2℃ / min respectively.
5. The evaluation method according to claim 4, characterized in that: The peak curing temperature is measured using differential scanning calorimetry.
6. The evaluation method according to claim 3, characterized in that: The curing time t cur1 ,t cur2 and t cur3 The corresponding values are (T cur1 -40)min, (T cur2 -10)min and (T cur3 -2)min.
Citation Information
Patent Citations
A tester and method for testing the thermal conductivity of pipes
CN103267774B
A method for testing the thermal conductivity of irregular samples
CN110220940B
Method for testing heat-conducting properties of lithium ion battery pole piece
CN111122647A
Device and method for testing heat-conducting property of thin film material
CN113092523A
Method for evaluating curing degree of main insulation of generator stator bar
CN113916929A